Meteorological Drought Analysis in Konya Closed Basin - Faize Sarış; Furkan Gedik (Coğrafya Dergisi)
In this study, meteorological drought condition in Konya Closed Basin was analyzed with the Standardized Precipitation Index (SPI) method by preparing 20 separate precipitation series at different temporal scales. Monthly total precipitation data of 11 meteorology stations in the basin recorded at different time spans between 1930-2019 were used. The data sets were prepared as short term (monthly, seasonal and 6 months) and long term (12, 24 and 36 months) precipitation series and the persistence component in SPI index values was statistically determined by applying the Run’s Test after SPI calculation. The severity of drought was evaluated according to different classes (mild, moderate, severe and extremely arid) in Konya closed Basin. The periods when moderate, severe and particularly extreme drought is evident are December, winter, 6 months and longer periods (12, 24, 36 months). As a result of the Run’s test, it was determined that the SPI values of 24 and 36 month series of all stations were statistically significant. Although some differences are observed between the stations in terms of dry years, a decadal variation for the prominent drought can be distinguished. Cihanbeyli, Beyşehir, Ereğli and Niğde for the 12-month period; Aksaray, Karaman, Seydişehir and Çumra for the 24-month period; and Konya, Kulu, Karapınar for the 36-month period have the highest number of dry years. These significant trends in prolonged droughts clearly indicate the propagation of drought severity in the Konya closed basin from meteorological to the agricultural and hydrological drought and the vulnerability of basin in terms of water renewal.